Evaluation of a core box produced by stereolithography in phenolic urethane cold box process - Lencina D.C. (2003)
The present study investigates the use of a core box produced by rapid prototyping (RP) technology called stereolithography (SL) in the Phenolic Urethane Cold Box (PUCB) process. This work describes a case study of the use of a core box produced by stereolithography in Osborn Cold Box® equipment. The core box has two cavities, one of them being covered with an electrodeposited copper layer. In this study aspects such as the most adequate surface finishing for a successful copper deposition and the life of the core box produced by stereolithography and copper coated stereolithography, in comparison with those traditionally manufactured by Ureol®, cast aluminum and cast iron machining, were analyzed. The study showed that the life of the core box manufactured by stereolithography was longer than those obtained by Ureol® and cast aluminum machining.